Antioxidants from Plants Protect against Skin Photoaging. (2nd August 2018) - Petruk, Ganna; Del Giudice, Rita; Rigano, Maria Manuela; Monti, Daria Maria
Abstract : Exposure to UV light triggers the rapid generation and accumulation of reactive oxygen species (ROS) in skin cells, with consequent increase in oxidative stress and thus in photoaging. Exogenous supplementation with dietary antioxidants and/or skin pretreatment with antioxidant-based lotions before sun exposure might be a winning strategy against age-related skin pathologies. In this context, plants produce many secondary metabolites to protect themselves from UV radiations and these compounds can also protect the skin from photoaging. Phenolic compounds, ascorbic acid and carotenoids, derived from different plant species, are able to protect the skin by preventing UV penetration, reducing inflammation and oxidative stress, and influencing several survival signalling pathways. In this review, we focus our attention on the double role of oxidants in cell metabolism and on environmental and xenobiotic agents involved in skin photoaging. Moreover, we discuss the protective role of dietary antioxidants from fruits and vegetables and report their antiaging properties related to the reduction of oxidative stress pathways.